The Role of Hypertension for Maternal Outcomes of Women with HELLP Syndrome – a Retrospective Study from a Tertiary Obstetric Center - Müller, Linda-Marie; Eveslage, Maria; Köster, Helen Ann; Willy, Kevin; Möllers, Mareike; Schmitz, Ralf; Oelmeier, Kathrin; Willy, Daniela (Geburtshilfe und Frauenheilkunde, 2024)
HELLP syndrome is a serious disorder that can occur in pregnancy; it has many possible complications and is associated with adverse maternal outcome. Due to the lack of predictive parameters for HELLP syndrome, finding the right time for delivery is challenging. In contrast to preeclampsia, hypertension is not an essential part of the diagnosis; nevertheless, many women with HELLP syndrome are hypertensive. The role and possible implications of hypertension in HELLP syndrome are not fully understood.In this retrospective cohort study, we analyzed the maternal outcomes of 59 patients diagnosed with HELLP syndrome. The patients were divided into three groups according to their blood pressure levels during their stay in hospital. These three groups were compared in terms of patient characteristics and maternal outcomes. A combined endpoint for adverse maternal outcome was defined which included blood pressure and antihypertensive medication at discharge from hospital, severe postpartum anemia, and eclampsia.Women with hypertensive crises had an unfavorable outcome compared to women with lower blood pressure levels. Patients with higher blood pressure during pregnancy were more likely to be hypertensive at discharge and needed a combination of antihypertensive agents significantly more often. The risk of an adverse maternal outcome increased with the severity of hypertension. An increase in systolic blood pressure by 10 mmHg raised the risk of an adverse outcome by 74% (95% CI: 1.22–2.66).Hypertension not only plays an important role in preeclampsia but also affects the outcomes of patients with HELLP syndrome. These patients need to be identified quickly and treated accordingly as they are at risk of cardiovascular impairment. Patients should be followed up closely after delivery to reduce cardiovascular morbidity.
Keywords: HELLP syndrome; arterial hypertension; hypertensive crisis; cardiovascular risk; hypertension in pregnancy